The predator becomes the prey: regulating the ubiquitin system by ubiquitylation and degradation - Weissman, Allan M.; Shabek, Nitzan; Ciechanover, Aaron (Nature reviews. Molecular cell biology, 2011)
Key Points Monomeric ubiquitin is relatively stable; however, it appears to be degraded by the proteasome following its own ubiquitylation, which is mediated by the thyroid receptor-interacting protein 12 (TRIP12) ligase. Ubiquitin is also degraded through two other mechanisms: along with the target substrate as part of the polyubiquitin chain attached to it, and along with a peptide attached, either linearly or in an isopeptide bond, to its carboxy-terminal Gly residue. Ubiquitin-protein ligases (E3s) are largely responsible for conferring substrate specificity to the ubiquitin–proteasome system (UPS). An increasing number of these ligases are being shown to be subject to self-ubiquitylation (also known as auto-ubiquitylation), ubiquitylation by heterologous ligases, or both. In some cases, both self-ubiquitylation and ubiquitylation by heterologous ligases lead to degradation of the protein. In other cases, self-ubiquitylation can regulate the cellular function of the ligase, whereas ubiquitylation by a heterologous E3 results in degradation of the target ligase. Other components of the UPS, including ubiquitin-conjugating enzymes (E2s) and deubiquitylating enzymes, are also subject to ubiquitylation. Components of the ubiquitin system are also subject to modification by other ubiquitin-like protein modifiers. The 26S proteasome is a stable, long-lived complex and is probably degraded through microautophagy. As part of the response to some specific cellular signals, such as oxidative stress, starvation, and stimulation of the NMDA ( N -methyl- D -aspartate) receptor, it is disassembled into its two subcomplexes, the 19S regulatory particle (RP) and the 20S catalytic (or core) particle (CP). The RP is probably disassembled into its individual subunits, which are degraded by the proteasome following ubiquitylation. Caspase-mediated cleavage of specific 19S subunits has also been shown to regulate proteasomal activity under certain conditions. The effect of disassembly of the 26S proteasome on the 20S complex has remained unclear: in some cases it was shown to inhibit its activity, to avoid damage of uncontrolled degradation, whereas in others cases it has been shown to stimulate activity and to efficiently remove — apparently in a ubiquitin-independent manner — excess damaged proteins. Ubiquitylation regulates essentially all of the intracellular processes in eukaryotes by modifying numerous cellular proteins in a spatially and temporally controlled manner. Many components of the ubiquitin–proteasome system are themselves modified by ubiquitylation; this regulates their activity or targets them for degradation. Ubiquitylation (also known as ubiquitination) regulates essentially all of the intracellular processes in eukaryotes through highly specific modification of numerous cellular proteins, which is often tightly regulated in a spatial and temporal manner. Although most often associated with proteasomal degradation, ubiquitylation frequently serves non-proteolytic functions. In light of its central roles in cellular regulation, it has not been surprising to find that many of the components of the ubiquitin system itself are regulated by ubiquitylation. This observation has broad implications for pathophysiology.